2006
DOI: 10.1007/s10531-005-1341-z
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variations in the Abundance of Sporophila Seedeaters in the Southern Neotropics: Contrasting the Effects of Agricultural Development and Geographical Position

Abstract: Human alterations of the habitat may interfere with the natural processes that determine spatial patterns of species abundance. We examine the geographical position hypothesis and the agricultural transformation hypothesis to explain spatial patterns in the abundance of seedeater species (Sporophila spp.) in the southern Neotropics. The geographical position hypothesis predicts decreasing abundance with increasing distance from the center to the edge of a species' geographical range, and the agricultural trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 17 publications
(22 reference statements)
3
9
0
1
Order By: Relevance
“…At present, <25% of these original grasslands remain uncultivated, and the network of protected grasslands in Argentina covers <1% of these habitats (Krapovickas and Di Giacomo 1998, Viglizzo et al 2001, Bilenca and Miñarro 2004. Although the effect of agricultural intensification and homogenization of the landscape toward cropland on the avifauna of the Pampas of central Argentina will depend on the sensitivity and plasticity of each species (Fraga et al 1998, Fernández et al 2003, Fraga 2003, Filloy and Bellocq 2006, we found that the distributions of most specialized grassland birds have declined over the same period in which large areas of our study area have been converted to intensive crop production. We believe that similar trends will be found for rarer and more endangered grassland specialists inhabiting the Pampas, for example, species that were not included in our statistical analyses like the Greater Rhea (Rhea americana), Elegant Crested-Tinamou (Eudromia elegans multiguttata), Bay-capped Wren-Spinetail (Spartonoica maluroides), Hudson´s Canastero (Asthenes hudsoni), and Bearded Tachurí (Polystictus pectoralis, AOP/ SADS 2008).…”
Section: Conservation Implicationsmentioning
confidence: 63%
“…At present, <25% of these original grasslands remain uncultivated, and the network of protected grasslands in Argentina covers <1% of these habitats (Krapovickas and Di Giacomo 1998, Viglizzo et al 2001, Bilenca and Miñarro 2004. Although the effect of agricultural intensification and homogenization of the landscape toward cropland on the avifauna of the Pampas of central Argentina will depend on the sensitivity and plasticity of each species (Fraga et al 1998, Fernández et al 2003, Fraga 2003, Filloy and Bellocq 2006, we found that the distributions of most specialized grassland birds have declined over the same period in which large areas of our study area have been converted to intensive crop production. We believe that similar trends will be found for rarer and more endangered grassland specialists inhabiting the Pampas, for example, species that were not included in our statistical analyses like the Greater Rhea (Rhea americana), Elegant Crested-Tinamou (Eudromia elegans multiguttata), Bay-capped Wren-Spinetail (Spartonoica maluroides), Hudson´s Canastero (Asthenes hudsoni), and Bearded Tachurí (Polystictus pectoralis, AOP/ SADS 2008).…”
Section: Conservation Implicationsmentioning
confidence: 63%
“…Birds of the genus Sporophila are widely distributed throughout South America and are highly appreciated for their beautiful singing capacity [ 76 , 77 ]. The prevalence of birds in this genus mentioned as being captured to be kept in cages (especially S .…”
Section: Resultsmentioning
confidence: 99%
“…Variation in local abundance was extreme across the ranges of most species. Although differences in abundance of at least one order of magnitude have been found in other studies encompassing the whole ranges of species (e.g., Brewer & Gaston, ; Curnutt, Pimm, & Maurer, ; Filloy & Bellocq, ), most studies evaluating spatial variation in abundance do not cover full ranges (Samis & Eckert, ). In general, we found that species with lower median densities showed more variation in density.…”
Section: Discussionmentioning
confidence: 85%
“…No single group of environmental correlates (habitat, topography and human pressure) stood out as particularly useful predictors, although more complex relationships with local abundances were found for pressurebased than for habitat correlates. Other authors have also found variability in response of abundance to pressure-based predictors in the Neotropics: Piana and Marsden (2014) found opposing responses to cattle grazing among different raptor species, and Filloy and Bellocq (2006) found mixed responses among Sporophila seedeaters to agricultural development. There is a long history of human alteration of environments on the Peruvian coast with cycles of agricultural expansion and contraction (Hocquenghem, 1998(Hocquenghem, , 1999Shimada & Shimada, 1985), which have surely influenced current patterns of distribution and abundance.…”
Section: Variation In Density Across Species' Rangesmentioning
confidence: 97%